Optimal orientation of injectors for efficient spray pattern of fuel flow in a diesel engine. (2021) - Mano Alexander, P.; Nandhakumar, S.; Seenivasan, S.; Ashfaq Ahamed, N.A.; Raj Kumar, P.
Abstract: The geometry of the diesel fuel injection nozzle and fuel flow characteristics in the nozzle significantly affects the processes of fuel atomization, combustion and formation of pollutants emissions in a diesel engine. A modern compression ignition engine should meet ecological and economical requirements. As the process of combustion, production of pollutants and noise emissions is mainly controlled by the process of fuel injection. Nowadays a lot of effort is put into the development of new and improvement of existing diesel fuel injection systems. This work mainly deals with the prediction of efficient spray pattern of fuel flow by obtaining optimal orientation for injectors. The orientations is analyzed using CFD. The injection and the fuel spray characteristics connected with the combustion chamber geometry control the combustion and pollutant formation processes. Therefore the engine operation characteristics could be improved by improving one of the above. But still the fuel injection nozzle presents quite a less researched area. Comparatively case 2 (3 mm lift) gave the better velocity flow coefficient.